Method for decolorizing cyanoethyltrimethoxysilane
By contacting cyanoethyl trimethoxysilane (CETMS) with wood-based activated carbon, the problem of CETMS colored liquid is solved, and its color is effectively removed, satisfying the industrial color for colorless or low color value adhesion promoters and coupling agent demand.
Patent Information
- Application Number
- CN202480002097.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-07
- Filing Date
- 2024-04-12
- Publication Date
- 2025-02-14
AI Technical Summary
Cyanoethyltrimethoxysilane (CETMS) is usually a colored liquid and is difficult to meet the industry's demand for colorless or low-color bonding promoters and coupling agents.
By contacting CETMS with wood-based activated carbon, the color of CETMS is removed by using the adsorption properties of activated carbon, thereby reducing its color value b*.
Effectively reduce the color of CETMS and reduce its b* value to <38, meeting the industry's requirements for colorless or low-color products.
Smart Images

Figure CN119452011A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit under 35 U.S.C. §119(e) of U.S. Provisional Patent Application Serial No. 63 / 471,512, filed on June 7, 2023. U.S. Provisional Patent Application Serial No. 63 / 471,512 is hereby incorporated by reference. Technical Field
[0003] A method for reducing the color of cyanoethyltrimethoxysilane is provided. More specifically, the method involves treating yellow cyanoethyltrimethoxysilane with activated carbon. Background Art
[0004] Cyanoethyltrimethoxysilane (CETMS) can be used as an adhesion promoter or coupling agent in siloxane compositions such as room temperature vulcanizable (RTV) polyorganosiloxane sealant compositions. CETMS can be prepared via the hydrosilylation reaction of acrylonitrile and trichlorosilane, followed by methoxylation. CETMS can also be prepared by the hydrosilylation reaction of trimethoxysilane and acrylonitrile. However, these processes have disadvantages, including that CETMS is generally a colored liquid. For example, cyanoethyltrimethoxysilane from Gelest, Inc. of Morrisville, Pennsylvania, USA is a pale yellow liquid. Summary of the invention
[0005] The method for removing the color of CETMS includes contacting the CETMS with wood-based activated carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 is a picture of a sample from Example 1. CETMS feed refers to the untreated starting material. The sample shows that when treated under the same conditions using the vibration test, the activated carbon sample ACTICARBON TM BGX removed most of the color from the CETMS. Other activated carbons that were not wood based did not perform as well. DETAILED DESCRIPTION
[0007] The cyanoethyl trimethoxysilane (CETMS) used in the method described above can be provided by any convenient means. The method for lightening the color of CETMS above optionally also includes preparing CETMS before step 1). For example, CETMS can be prepared by a process including the hydrosilylation reaction of acrylonitrile and trichlorosilane, followed by methoxylation. Alternatively, CETMS can be prepared by a process including the hydrosilylation reaction of trimethoxysilane and acrylonitrile. Alternatively, CETMS can be prepared by a method including the transesterification reaction of cyanoethyl triethoxysilane (CETES) and methanol, wherein CETES can be prepared in the following manner: the hydrosilylation reaction of trichlorosilane and acrylonitrile to prepare cyanoethyl trichlorosilane, followed by ethoxylation of the cyanoethyl trichlorosilane (using ethanol). Without wishing to be bound by theory, it is believed that the impurities that impart color to CETMS may be the result of the above-mentioned hydrosilylation reaction.
[0008] More specifically, the transesterification process for preparing CETMS may include:
[0009] 1) combining starting materials comprising: (A) cyanoethyltriethoxysilane (CETES), (B) a stoichiometric excess of methanol, and (C) an acid catalyst; thereby producing a transesterification reaction mixture;
[0010] Optionally 2) adding (D) activated carbon to the transesterification reaction mixture;
[0011] 3) removing substances comprising methanol, ethanol and (C) an acid catalyst from the transesterification reaction mixture; and
[0012] 4) Repeating steps 1) to 3) one or more times (a total of at least two additions of methanol and (C) acid catalyst and subsequent removal of methanol, ethanol and catalyst).
[0013] In the process for preparing CETMS, the transesterification reaction of CETES with methanol can be carried out according to the transesterification reaction scheme shown below.
[0014]
[0015] In the formula of the alkoxysilane product, when x=0, the formula is CETMS. However, partially methoxylated substances, such as cyanoethyl-silane, diethoxy-silane, monomethoxy-silane (where x=2) and / or cyanoethyl-silane, monoethoxy-silane, dimethoxy-silane (where x=1) can also be formed during the process described herein. In the formula of the dimer in the reaction scheme, each R is independently selected from the group consisting of methyl and ethyl. Dimers are by-products that may be formed during the process described herein, and increasing the formation of dimers can adversely affect the yield of CETMS. It is desirable to drive the reaction to achieve high conversion of ethoxy groups in CETES to methoxy groups, high purity CETMS and low amount of dimer formation.
[0016] In step 1) of the transesterification process for preparing CETMS described herein, (A) CETES and (B) methanol are used in an amount sufficient to provide a stoichiometric excess of methanol. The amount of (A) CETES and (B) methanol may be at least 5:1 (B): (A) (molar ratio), alternatively at least 15:1, while (B): (A) may be up to 30:1, alternatively up to 15:1. Alternatively, (B): (A) may be 5:1 to 30:1, alternatively >5:1 to 30:1 and alternatively 15:1 to 30:1. Without wishing to be bound by theory, it is believed that step 1) may be carried out at RT or at an elevated temperature, such as up to 70°C. Alternatively, the temperature may be from 21°C to 70°C. The time for the transesterification reaction in step 1) is sufficient to reach equilibrium. For example, at RT, the time may be from 1 hour to 4 hours. However, the exact time will depend on various factors, such as the selected temperature and the choice and amount of (C) acid catalyst. Without wishing to be bound by theory, it is believed that carrying out the transesterification reaction in step 1) at RT may be effective in terms of time, energy and cost associated with heating and cooling. The use of an acid catalyst can provide the benefit of being able to react quickly at RT, which minimizes time and operating costs. The reaction can optionally be carried out at an elevated temperature. In addition, step 1) can be carried out under conditions that minimize or eliminate the presence of moisture. Without wishing to be bound by theory, it is believed that moisture contamination may trigger the formation of dimers that will deviate from the side reaction of the CETMS yield when maximizing the CETMS yield.
[0017] Starting material (C) acid catalyst can be selected from the group consisting of the following items: hydrogen halide, such as hydrogen halide of formula HX, wherein X is Cl, Br or I; sulfonic acid (such as toluenesulfonic acid or trifluoromethanesulfonic acid); and ion exchange resin. Alternatively, (C) acid catalyst can be hydrogen halide, and alternatively acid catalyst can be HCl. When (C) acid catalyst is hydrogen halide (e.g., HCl), based on the weight of (A) CETES and the weight of (B) MeOH combined, hydrogen halide (e.g., HCl) can be used in an amount of at least 1ppm, alternatively at least 5ppm, alternatively at least 10ppm, alternatively at least 30ppm, while the amount of hydrogen halide (e.g., HCl) can be at most 100ppm, alternatively at most 50ppm, alternatively at most 30ppm. Alternatively, based on the same benchmark, the amount of hydrogen halide (e.g., HCl) can be 10ppm to 100ppm, alternatively 10ppm to 50ppm and alternatively 30ppm. Alternatively, when an ion exchange resin is used, the amount may be at least 0.1% solid to liquid, alternatively at least 0.5%, while at the same time the amount may be up to 30%, based on the same basis. Alternatively, the amount of ion exchange resin may be from 0.1% to 30%.
[0018] The starting materials used in step 1) of the process are known in the art and are commercially available. CETES is purchased from Gelest, Morrisville, Pennsylvania, USA as a pale yellow liquid, and CETES is purchased from TCI America as a yellow liquid. MeOH and HCl are available from various sources, including Sigma-Aldrich, Inc. of St. Louis, Missouri, USA. The ion exchange resins may be strong acid and weak acid cation exchange resins used herein, wherein the ionic form of the resin is not hydrogen (H+). Such ion exchange resins are commercially available, such as DOWEX TM Monosphere 2030, DOWEX TM MARATHON TM AMBERLITE 1200 (Na+ form) and AMBERLITE IR122Na are commercially available from TDCC.
[0019] The combination of starting materials in step 1) of the transesterification process can be carried out in batches or continuously and by any convenient means (such as mixing). Mixing can be carried out in conventional equipment, such as a batch reactor equipped with an agitator and optionally a heating device (such as a jacket). Alternatively, the process can be carried out in a packed bed reactor, for example, when a solid catalyst (e.g., an ion exchange resin) is used and / or when there is step 2) (e.g., using activated carbon), the reactor can be filled with (C) an acid catalyst.
[0020] Step 2 of the process) includes merging (D) activated carbon and the transesterification reaction mixture prepared in step 1). Step 2) is optional. However, when used, step 2) can be carried out at RT, for example, by mixing the activated carbon with the transesterification reaction mixture prepared in step 1) for a time sufficient to adsorb the acid HCl therefrom. The exact time depends on various factors, such as the size of the container for step 2) (which may be the same as the reactor for step 1)), however, the time may be at least 1 hour, alternatively at least 2 hours, alternatively at least 4 hours, alternatively at least 8 hours and alternatively at least 16 hours; while the time may be at most 48 hours, alternatively at most 24 hours and alternatively at most 16 hours. Step 2) may be carried out under conditions of minimizing or eliminating moisture to prevent dimer formation and maximizing CETMS yield.
[0021] When step 2) is present, (D) activated carbon may be selected from the group consisting of: (D1) bituminous coal activated carbon; (D2) coconut activated carbon having an iodine value of ≥ 1200 mg / g; and (D3) a combination of (D1) and (D2). (D1) Bituminous coal activated carbon and (D2) coconut activated carbon are known in the art and are commercially available from various sources, such as General Carbon Corporation of Paterson, New Jersey, USA or Calgon Carbon of Pittsburgh, Pennsylvania, USA. The bituminous coal activated carbon may have an iodine value of at least 500 mg / g(min), alternatively at least 600 mg / g(min), alternatively at least 750 mg / g(min), alternatively at least 850 mg / g(min), alternatively at least 900 mg / g(min), while the bituminous coal activated carbon may have an iodine value of at most 1200 mg / g(min), alternatively at most 1,100 mg / g(min), alternatively at most 1,000 mg / g(min), alternatively at most 950 mg / g(min). Alternatively, the iodine value of the bituminous coal activated carbon may be 600 mg / g(min) to 1200 mg / g(min), alternatively 750 mg / g(min) to 1200 mg / g(min), 900 mg / g(min) to 1200 mg / g(min), and alternatively 900 mg / g(min) to 1050 mg / g(min). The coconut activated carbon may have an iodine value of ≧1200 mg / g(min), alternatively from 1,200 mg / g(min) to 1,500 mg / g(min), and alternatively from 1,200 mg / g(min) to 1,300 mg / g(min).
[0022] Examples of bituminous coal activated carbon include GC 12×40, which is a native activated carbon in granular form having an iodine value of 900 mg / g(min) and a density of 0.47 g / cc to 0.53 g / cc and is commercially available from General Carbon Corporation; and CAL TM 12×40 granular activated carbon, which is a reagglomerated metallurgical grade bituminous coal with an iodine value of 1000 mg / g(min), is commercially available from Calgon Carbon. Other bituminous coal activated carbons from Calgon Carbon include CPG TM LF 12×40, which has an iodine value of 950 mg / g(min); FILTRASORB TM 300M, which has an iodine value of 900 mg / g(min); FILTRASORB TM400M, which has an iodine value of 1000 mg / g(min); HPC MAXX, which has an iodine value of 900 mg / g; and SGL8×20, which is a granular activated carbon made from bituminous coal combined with a binder and having an iodine value of 900(min) mg / g. Coconut activated carbon includes OLC Plus 12×30, which has an iodine value of 1200 mg / g(min) and a density of 0.45 g / cc, and OLC Plus 12×30 is also available from Calgon Carbon.
[0023] When step 2) is present (i.e., using activated carbon), the process may further include treating the activated carbon prior to use in step 2). The treatment may be performed to, for example, dry the activated carbon (e.g., to remove all or a portion of any adsorbed moisture to minimize the likelihood of hydrolysis of the alkoxysilane product when the carbon is in contact with the transesterification reaction mixture). For example, the activated carbon may be heated to a temperature above the boiling point of water (e.g., >100°C, alternatively >100°C to 200°C, alternatively 120°C to 160°C) for a time sufficient to remove all or a portion of the water, e.g., 1 minute to 24 hours. The activated carbon may be heated at ambient pressure or at reduced pressure. Prior to use in step 2), the activated carbon may be heated and stored under an inert atmosphere (such as nitrogen).
[0024] Step 3) of the process comprises removing materials comprising (excess) unreacted (B) methanol, ethanol (which is produced as a byproduct) and (C) acid catalyst from the transesterification reaction mixture. Step 3) can be carried out in any convenient manner. Step 3) can include filtering, for example to remove solid matter, such as removing ion exchange resins when used as (C) acid catalyst, and / or removing activated carbon when step 2) is present. Step 3) can also include stripping and / or distillation under heating and optionally reduced pressure, which can remove methanol, ethanol and liquid acid catalysts (such as HCl).
[0025] The step 4) of the transesterification reaction process producing CETES includes repeating steps 1) to 3) one or more times. Step 4) may include repeating 1) to 3) at least once, alternatively one to four times. Without wishing to be bound by theory, it is believed that repeating steps 1) to 3) too many times (e.g., five times or more (alternatively 5 times or more)) (i.e., adding methanol and acid catalyst and subsequent removal six to seven times or more in total) may lead to the formation of a large amount of undesirable dimers and / or increase costs, which makes the process impractical on a commercial scale. Alternatively, step 4) may include repeating steps 1) to 3) once or twice, particularly when there is step 2). Without wishing to be bound by theory, it is believed that due to thermodynamic equilibrium limitations and the higher volatility of methanol over ethanol, a reverse reaction may occur during step 3) (e.g., by stripping and / or distillation) through the reaction of CETMS (where x=0 in the formula of the alkoxylated product shown above) or partially methoxylated material (where x=1 or 2) with the EtOH byproduct, which byproduct cannot be removed until all or a significant portion of the lower boiling MeOH is first removed. In addition, the inventors surprisingly discovered that treating the transesterification reaction mixture with activated carbon in step 2) minimizes this reverse reaction. Because each repetition of steps 1) to 3) increases the cost of the process, it is desirable to minimize the number of repetitions in step 4) to achieve efficiency while achieving the yield and purity of the CETMS product.
[0026] The above-mentioned transesterification process produces a composition comprising a composition having the formula The conversion of ethoxy groups of the CETES starting material to methoxy groups may be at least 90 GC area %, alternatively at least 91 GC area %, alternatively at least 92 GC area %, alternatively at least 93 GC area % and alternatively at least 94 GC area %, while at the same time, the conversion may be at most 100 GC area %, alternatively at most 99 GC area %, alternatively at most 98 GC area %, alternatively at most 97 GC area % and alternatively at most 96 GC area %, as measured by the test method described below and used in the examples. The purity of CETMS can be at least 72 GC area%, alternatively at least 81 GC area%, alternatively at least 86 GC area%, alternatively at least 89 GC area% and alternatively at least 90 GC area%, while at the same time, the purity of CETMS can be at most 100 GC area%, alternatively at most 98 GC area%, alternatively at most 95 GC area%, alternatively at most 92 GC area% and alternatively at most 90 GC area%, as measured by the test method described below and used in the examples. The amount of dimer can be 0 wt %, alternatively 1 wt % to 10 wt %, alternatively 1.5 wt % to 9 wt %, alternatively 1.8 wt % to 6 wt %, alternatively 2 wt % to 3 wt %. However, the amount of dimer can vary depending on whether step 2) is present. For example, when step 2 of the process is omitted) (no treatment agent is used), the amount of dimer may be 1 wt% to 3 wt%, alternatively 1.5 wt% to 2 wt%, and alternatively 1.8 wt%. When a treatment agent (e.g., activated carbon) is used, the amount of dimer may be 5 wt% to 10 wt%, alternatively 6 wt% to 9 wt%.
[0027] Alternatively, the above-mentioned transesterification reaction process can be modified to produce CETMS that also contains dimers. In the above-mentioned transesterification reaction process, water can be optionally added in step 1), for example, by merging water with methanol before step 1). Water is generally not limited and can be used in pure form (that is, without or substantially without minerals and / or other impurities). Alternatively, water can be treated or not treated before adding in the above-mentioned step 1). Examples of processes that can be used for purifying water include distillation, filtration, deionization, and a combination of two or more thereof, so that water can be deionized, distilled and / or filtered. Alternatively, water can be untreated (for example, it can be tap water, that is, provided by a municipal water supply system or well water, and is used without further purification). Water can be used in the amount selected by those skilled in the art, depending on various factors, such as the desired amount of dimers to be formed in the reaction product, the reaction parameters adopted, the reaction magnitude, and the species of the selected acid catalyst. However, based on the weight of (B) methanol, the amount of water can be 0.05% to 1%.
[0020] The process produces a composition, which comprises:
[0028] Mode The alkoxysilane product, and
[0029] Mode
[0030] A dimer of wherein R and x are as described above. Alternatively, each R may be methyl. Alternatively, each x may be 0. Alternatively, the composition may comprise:
[0031] With formula Cyanoethyltrimethoxysilane (CETMS) and its Dimer. Alternatively, the composition may be substantially composed of CETMS and its dimer. Alternatively, the composition may be composed of CETMS and its dimer. Alternatively, the composition may be substantially free of or free of methoxy groups in alkoxysilane products and dimers. In the above process, the conversion rate of the ethoxy groups of the CETES starting material to methoxy groups may be at least 90 GC area%, alternatively at least 91 GC area%, alternatively at least 92 GC area%, alternatively at least 93 GC area% and alternatively at least 94 GC area%, while at the same time, the conversion rate may be at most 100 GC area%, alternatively at most 99 GC area%, alternatively at most 98 GC area%, alternatively at most 97 GC area% and alternatively at most 96 GC area%, as measured by the test method described below and used in the examples. The purity of CETMS may be at least 72 GC area %, alternatively at least 81 GC area %, alternatively at least 86 GC area %, alternatively at least 89 GC area % and alternatively at least 90 GC area %, while at the same time, the conversion of ethoxy groups may be at most 100 GC area %, alternatively at most 98 GC area %, alternatively at most 95 GC area %, alternatively at most 92 GC area % and alternatively at most 90 GC area %, as measured by the test method described below and used in the examples. The amount of dimer may be at least 20 wt % (based on the combined weight of the alkoxysilane product and the dimer), based on the same basis, alternatively 20 wt % to 30 wt %, alternatively 20 wt % to 29 wt %, alternatively 20 wt % to 28 wt %, alternatively 20 wt % to 27 wt % and alternatively 20 wt % to 26 wt %. Without wishing to be bound by theory, it is believed that when a product containing dimer in an amount of 20 to 30 wt % is used in a polyorganosiloxane composition, the cured product of the composition may have improved adhesion compared to a cured product of a composition containing CETMS having a lower amount of dimer.
[0032] According to the color value measurement results in the following examples, the products prepared by any of the above processes contain CETMS that generally have a light yellow to yellow color, ie, a b* value ≥ 38, alternatively 38 to 60.
[0033] There is a need in the industry for adhesion promoters and coupling agents that are colorless or have low color values (i.e., b* values <38, alternatively b* values of 0 to 10, as measured by the color value measurement process described in the Examples below) so that these additives do not adversely affect the color of the desired product. For certain (e.g., colorless or white) polyorganosiloxane compositions, it is undesirable to include colored (e.g., pale yellow or yellow) components that may adversely affect the appearance of the final cured polyorganosiloxane product, such as a sealant. The method of the present invention is used to reduce the b* value of CETMS to <38, alternatively <10, alternatively to a value of 0 to 10.
[0034] Method for lightening the color of CETMS
[0035] Methods for lightening the color of cyanoethyltrimethoxysilane (CETMS) include:
[0036] 1) contacting a CETMS having a color value b* ≥ 38 with wood-based activated carbon for a time sufficient to reduce the b* of the CETMS to < 38, and
[0037] 2) Separation of wood-based activated carbon from cyanoethyltrimethoxysilane.
[0038] The method for removing the color of CETMS described above includes step 1), which includes contacting CETMS with a b* value ≥ 38 (and which can be prepared by any of the above processes) with wood-based activated carbon. Contacting CETMS with wood-based activated carbon can be carried out in any convenient manner. For example, a continuous mode may include pumping CETMS through a container, such as a drum or bed, containing a wood-based activated carbon packed bed. The size of the bed may be sufficient to reduce the b* value to <38 after a single pass, and alternatively multiple passes may be used to reduce the b* value to <38, alternatively <20, alternatively <18, alternatively ≤10, alternatively <10 and alternatively 0 to 10. Alternatively, in a batch mode, wood-based activated carbon may be added to CETMS, such as in a container for preparing CETMS, and then the wood-based activated carbon may be removed, for example, by filtration. This may be repeated one or more times until CETMS has a b* value as described above. The amount of wood-based activated carbon depends on various factors, including the b* value of the CETMS to be treated and whether continuous mode or batch mode will be used. For example, step 1) may include mixing 93 wt % to 99 wt % CETMS and 1 wt % to 7 wt % wood-based activated carbon in batch mode.
[0039] The wood-based activated carbon used to remove the color of CETMS is different from the bituminous coal activated carbon or coconut activated carbon used in the transesterification reaction process for preparing CETMS described above. Wood-based activated carbon (which may be referred to as plant-derived activated carbon, depending on the brand selected) can be used in the present invention. The wood-based activated carbon may have phosphoric acid within the pore structure. Optionally, the wood-based activated carbon is activated with phosphoric acid prior to step 1). Wood-based activated carbon produced by phosphoric acid activation is commercially available from various sources, such as ACTICARBONE from Calgon Carbon Corporation. TM BGE and ACTICARBONE TM BGX products and NORIT Activated Carbon from Norit Activated Carbon of Marshall, Texas, USA TM CNSP and NORIT TM C Gran. Phosphoric acid activation can produce a 1500m 2 / g-2500m 2 Very high surface area carbons in the 1000 g / cm2 range are available commercially in granular, pellet, or powder form from a variety of sources including Calgon Carbon Corporation or Carbon Activated Corp. of Compton, California, USA. Wood-based activated carbons may have an iodine number of >600 (alternatively >600 to 1500) or a molasses number of >150. Wood-based activated carbons may have an iodine number of 0.22 g / cm2. 3 Up to 0.24g / cm 3 The apparent density of .
[0040] The method for removing the color of CETMS may optionally further comprise one or more additional steps. For example, the method may optionally further comprise drying the wood-based activated carbon prior to contacting with CETMS in step 1).
[0041] Step 2) of the above method may be performed by any convenient means. For example, step 2) may comprise filtering the CETMS after step 1) to thereby remove the wood-based activated carbon.
[0042] How to use
[0043] CETMS having a color value b*<38, alternatively 0 to 10, produced as described above can be used in polyorganosiloxane compositions, such as room temperature vulcanizable organopolysiloxane compositions. RTV organopolysiloxane compositions are known in the art, such as those disclosed in: U.S. Patent No. 4,483,973 to Lucas et al.; U.S. Patent No. 5,962,559 to Lucas et al.; U.S. Patent No. 7,550,548 to Hatanaka et al.; U.S. Patent No. 7,674,871 to Koch et al.; U.S. Patent Application Publication No. 2007 / 0173597 to Williams et al.; and PCT Patent Application Publication No. WO2007 / 024792. CETMS can act as an adhesion promoter, coupling agent and / or crosslinking agent in the polyorganosiloxane composition. Alternatively, the reaction product can be added to a commercially available RTV sealant, such as XIAMETER® from TDCC. TM SLT-5200. Without wishing to be bound by theory, it is believed that polyorganosiloxane compositions containing CETMS prepared as described herein can be used in white or colorless sealants due to the low b* color value of CETMS.
[0044] Example
[0045] The following examples are provided to illustrate the invention to those skilled in the art and these examples should not be construed as limiting the scope of the invention set forth in the claims.The adsorbents were obtained and prepared as follows: The adsorbents received as received from the supplier had different concentrations of moisture.
[0046] Table 1 - Adsorbents and CETES Feeds
[0047]
[0048] All adsorbents were thoroughly dried in a vacuum oven at 130°C for 16 hours. After drying, the adsorbents were removed from the hot oven and placed in wide-mouth bottles. The wide-mouth bottles were then stored in a dry box.
[0049] In this Example 1, the adsorbents were screened in the shaking test as follows: Using the adsorbent that was dried and stored in a dry box, the adsorbent was weighed and added to a glass vial in a fume hood based on the desired ratio of solid to liquid. CETMS was then added to the vial. Once the addition was complete, the vial was placed on a wrist shaker and allowed to shake for 24 hours.
[0050] After shaking for 24 hours, the vials were returned to the fume hood. The treated CETMS were analyzed as follows to determine the effect of the adsorbent: The contents of each vial were filtered using a 5 mL syringe with a thread on a 0.45 micron filter. The effluent from the filter was a clear liquid free of adsorbent fines. The clear liquid was sent for color testing.
[0051] Color measurements were performed using a Konica Minolta CM-5 spectrophotometer with a C illuminant and a 2° observer. Colors were reported as L*, a*, and b* measurements. The primary measurement used was b*, which is a measure of blue and yellow, where the greater the b*, the more yellow the color. L* and a* values were also recorded, where L* is a measure of brightness, 100 being the brightest, and a* is a measure of green and red, where positive numbers are red and negative numbers are green.
[0052] Table 1 shows the color results of different activated carbons with the same solid-to-liquid ratio (i.e. 3% solid, 97% liquid). As can be seen in Table 2, Acticarbone, an acidic wood-based activated carbon, TM BGX shows the lowest b-value (least yellow).
[0053] Table 2 - Color Measurements
[0054]
[0055] In this Example 2, the vibration test was performed as described in Example 1, but the amount of activated carbon and CETMS was varied. The activated carbon, amount, and color test results are shown below in Table 3. The data in Table 3 show that under otherwise identical processing conditions, 7% ACTICARBONE BGX provides better color reduction than 10% and 12% CAL 12X40.
[0056] Table 3 - Vibration test results using different amounts of activated carbon
[0057]
[0058]
[0059] In this Example 3, the vibration test was performed as described in Example 1, but using different wood-based activated carbon and bituminous coal-based activated carbon CAL 12x40 at 3% loading each. These activated carbons were tested and the results are given in Table 4. The data in Table 4 show that under otherwise identical conditions, all of the wood-based activated carbons tested provided better color reduction than the bituminous coal-based activated carbon.
[0060] Table 4 - Vibration test results of bituminous coal-based activated carbon and wood-based activated carbon
[0061]
[0062] In this Example 4, vibration testing was performed as described in Example 1, but using different amounts of activated carbon, as shown below in Table 5. The data in Table 5 shows that ACTICARBONE BGX provides superior color reduction than CAL12X40 at every loading tested.
[0063] Table 5
[0064]
[0065]
[0066] In this Example 5, a single-pass continuous process for removing CETMS color was modeled as follows: Activated carbon was packed into a column having a length of 18 inches (45.72 cm) and a diameter of 3 inches (7.62 cm) (length / diameter L / D ratio = 6). CETMS with a color value of b* = 38 was pumped to the column inlet at 50 g / min. Samples were collected at the column outlet and analyzed for color. The operating conditions are shown in Table 6 below.
[0067] Table 6—Single Pass Column Experiment
[0068] experiment 5-1 5-2 Adsorbent ACTICARBONE BGX CAL 12X40 The mass of carbon filled in the column (g) 474.3 1003.8
[0069] Filled with ACTICARBONE TM The columns of BGX provide better color reduction than the columns filled with CAL 12X40, even though (due to density differences) the columns containing CAL 12X40 are lighter than those containing ACTICARBONE. TM The column of BGX accommodates more than twice the mass of activated carbon. Samples were taken from the column effluent at different times and the color was measured as described above. The results are shown in Table 7 below.
[0070] Table 7 - Color results obtained from a single-pass continuous process
[0071]
[0072]
[0073] Adsorbent Cal12x40 Time [hours] b*(C) 0.73 6.97 1.22 8.73 1.52 9.75 2.22 12.73 2.70 13.66 3.58 14.86 4.58 15.78 5.42 16.46
[0074] The data in Table 7 show that the ACTICARBONE TM BGX provides better color reduction than the CAL12X40 used in Experiment 5-2, even though a larger mass of CAL12X40 activated carbon was used compared to the amount used in Experiment 5-1. These data indicate that not only ACTICARBONE TMBGX provides better color reduction than CAL12X40, and when using ACTICARBONE TM When using BGX, the process can run longer before the activated carbon needs to be replaced or regenerated.
[0075] Test Method
[0076] Gas chromatography (GC) was used to verify the composition of the material. All reported compositions in the above examples are based on GC area%. An Agilent 7890A GC system with helium carrier gas and FID detector was used with Restek Rtx-130m×0.25mm×1um. The flow rate was set to a constant flow rate of 1.5mL / min. The gradient started at 40°C, held at temperature for 2 minutes, and then heated to 260°C at 20°C / min. The final temperature of 260°C was maintained for 2 minutes.
[0077] Other conditions used were:
[0078] 1. Injection volume 1uL
[0079] 2. For solvent A and solvent B washes, use acetonitrile needle washes
[0080] 3. Split / non-split inlet temperature and FID temperature 260℃
[0081] 4. Split injection with a split ratio of 50:1
[0082] Titration was performed with a Metrohm Brinkmann 776 Dosimat to determine chloride levels with BCP indicator and 0.1 N KOH.
[0083] Industrial Applicability
[0084] CETMS can be used as an adhesion promoter or coupling agent in polyorganosiloxane compositions such as room temperature vulcanizable polyorganosiloxane sealant compositions. However, CETMS is not widely commercially available, and commercially available CETMS generally have the disadvantage of being light yellow or yellow. There is an industrial need for polyorganosiloxane compositions containing CETMS that are cured to form a colorless or white cured product. Therefore, it is desirable to provide CETMS with a light color or no color, i.e., a b* value of 0 to 10 according to the color measurement process described in the above examples.
[0085] Definition and Use of Terms
[0086] The amount of all starting materials in the composition is 100% by weight. Unless otherwise specified in the context of this specification, all quantities, ratios and percentages are by weight. Summary of the invention and description abstract are hereby incorporated by reference. Unless otherwise specified in the context of this specification, the articles "one", "a kind of" and "said" refer to one (a kind) or more (multiple). Unless otherwise specified in the context of this specification, the singular form also includes the plural form. Each embodiment or alternative proposed herein can be combined with any other embodiment or alternative. The term "comprising" and its derivative meaning, such as "having" and "containing" are used in this article with its broadest sense, meaning and covering the concept of "including", "essentially consisting of..." and "consisting of...". Using "for example", "for example", "such as" and "including" to list exemplary examples does not mean to be limited to the listed examples. Therefore, "for example" or "such as" means "for example, but not limited to" or "such as, but not limited to" and covers other similar or equivalent examples.
[0087] It should be understood that the appended claims are not limited to the specific and particular compounds, compositions or methods described in the detailed description, which may vary between specific embodiments falling within the scope of the appended claims. With respect to any Markush group used herein to describe specific features or aspects of various embodiments, different, special and / or unexpected results can be obtained from each member of each Markush group independent of all other Markush members. Each member of the Markush group can be relied upon individually and / or in combination and provides sufficient support for specific embodiments within the scope of the appended claims.
[0088] The abbreviations used in this application are defined in Table 8 below.
[0089] Table 8 - Abbreviations
[0090] abbreviation definition AN Acid value ℃ Celsius C Cubic centimeters CETES Cyanoethyltriethoxysilane CETMS Cyanoethyltrimethoxysilane EtOH Ethanol g gram GC Gas chromatography HDPE High Density Polyethylene hr Hour L Lift M Moore MeOH Methanol mg mg mmHg mmHg N normal OZ ounce RT Room temperature 23℃±2℃ RTV Room temperature vulcanizable TDCC The Dow Chemical Company, Midland, Michigan, USA u ul um Micrometer wt weight
[0091] Embodiments of the present invention
[0092] In a first embodiment, a method for manufacturing a CETMS comprises:
[0093] I) preparing CETMS by an ester exchange reaction process, the ester exchange reaction method comprising 1) combining starting materials comprising the following items
[0094] (A) Cyanoethyltriethoxysilane (CETES),
[0095] (B) a stoichiometric excess of methanol, and
[0096] (C) an acid catalyst, thereby producing a transesterification reaction mixture;
[0097] Optionally 2) adding (D) activated carbon to the transesterification reaction mixture;
[0098] 3) removing substances comprising methanol, ethanol and (C) an acid catalyst from the transesterification reaction mixture; and
[0099] 4) repeating steps 1) to 3) one or more times (a total of at least two additions of methanol and (C) an acid catalyst and subsequent removal of methanol, ethanol and catalyst); thereby producing a transesterification product comprising CETMS having a color b* value ≥ 38;
[0100] II) contacting the CETMS having a color value b*>30 with wood-based activated carbon for a time sufficient to reduce the b* of cyanoethyltrimethoxysilane to <38; and
[0101] III) Separation of wood-based activated carbon from cyanoethyltrimethoxysilane.
[0102] In a second embodiment, in the method according to the first embodiment, step I) further comprises adding water in an amount of 0.05 wt % to 1 wt % based on the weight of (B) methanol.
[0103] In a third embodiment, in step II) of the process according to the second embodiment, the wood-based activated carbon is activated with phosphoric acid before step 1).
[0104] In a fourth embodiment, in step II) of the method according to any of the preceding embodiments, the wood based activated carbon has an iodine value >600.
[0105] In a fifth embodiment, in step II) of the method according to any one of the preceding embodiments, the wood-based activated carbon has a carbon content of 0.22 g / cm 3 Up to 0.24g / cm 3 density.
[0106] In a sixth embodiment, in step II) of the method according to any one of the preceding embodiments, the wood-based activated carbon comprises ACTICARBONE TM BGX、ACTICARBONE TM BGE, NORIT TM CNSP、NORIT TM C Gran or a combination thereof.
[0107] In a seventh embodiment, in the method according to any one of the preceding embodiments, step 2) is present during the transesterification reaction.
[0108] In an eighth embodiment, in the method according to the seventh embodiment, the activated carbon added in step 2) is selected from bituminous coal activated carbon and coconut activated carbon.
Claims
1. A method for reducing the color of cyanoethyltrimethoxysilane, wherein the method comprises: 1) contacting cyanoethyltrimethoxysilane having a color value b* ≥ 38 with wood-based activated carbon for a time sufficient to reduce the b* of the cyanoethyltrimethoxysilane to < 38, and 2) Separating the wood-based activated carbon from the cyanoethyltrimethoxysilane.
2. The method according to claim 1, wherein the wood-based activated carbon is activated with phosphoric acid prior to step 1).
3. A method according to claim 1 or claim 2, wherein the wood based activated carbon has an iodine value of >600.
4. The method according to any one of claims 1 to 3, wherein the wood-based activated carbon has a carbon density of 0.22 g / cm 3 Up to 0.24g / cm 3 density.
5. The method according to any one of claims 1 to 4, wherein the wood-based activated carbon comprises ACTICARBONE TM BGX、ACTICARBONE TM BGE, NORIT TM CNSP、NORIT TM C Gran or a combination thereof.
6. The method according to any one of claims 1 to 5, wherein step 1) comprises mixing 93 to 99 wt% of the cyanoethyltrimethoxysilane with 1 to 7 wt% of the wood-based activated carbon in batch mode.
7. The method according to any one of claims 1 to 5, wherein step 1) comprises flowing the cyanoethyltrimethoxysilane through a packed bed of the wood-based activated carbon in a continuous process.
8. The method according to any one of claims 1 to 7, wherein step 2) comprises filtering the cyanoethyltrimethoxysilane after step 1), thereby removing the wood-based activated carbon.
9. The method according to any one of claims 1 to 8, wherein the method further comprises preparing the cyanoethyltrimethoxysilane by a process comprising a hydrosilylation reaction of acrylonitrile and trichlorosilane followed by methoxylation before step 1).
10. The method according to any one of claims 1 to 8, wherein the method further comprises preparing the cyanoethyltrimethoxysilane by a process comprising a hydrosilylation reaction of trimethoxysilane and acrylonitrile before step 1).
11. The method according to any one of claims 1 to 8, wherein the method further comprises preparing the cyanoethyltrimethoxysilane through a process comprising a transesterification reaction of cyanoethyltriethoxysilane with methanol before step 1).
12. The method of claim 11, wherein the process further comprises adding water, thereby producing dimers.
13. The method according to claim 11 or claim 12, wherein the transesterification reaction is carried out by: i) combining the starting materials comprising (A) cyanoethyltriethoxysilane, (B) a stoichiometric excess of methanol, optional water, and (C) an acid catalyst, thereby producing a reaction mixture; and Optionally ii) adding to the reaction mixture (D) activated carbon selected from the group consisting of (D1) Bituminous coal activated carbon, (D2) coconut activated carbon having an iodine value of at least 1200 mg / g, and (D3) both (D1) and (D2); iii) removing materials comprising methanol, ethanol and the acid catalyst from the reaction mixture; and iv) repeating steps i) to iii) one or more times, thereby forming a reaction product comprising the cyanoethyltrimethoxysilane.
14. The method according to claim 12 or claim 13, wherein (C) the acid catalyst is selected from the group consisting of HCl and ion exchange resins.
15. The method according to claim 13 or claim 14, wherein in step i), the amount of water is 0.05 wt% to 1 wt% based on the weight of (B) the methanol.
Citation Information
Patent Citations
Sealant composition containing inorganic-organic nanocomposite filler
US20070173597A1
Adhesion promoters for one-component RTV silicone compositions
US4483973A
Neutral cure one component room temperature vulcanizable silicone compositions
US5962559A
Room-temperature-curable organopolysiloxane composition
US7550548B2
Fast curing polydiorganosiloxanes
US7674871B2